Two new species of lotic breeding salamanders (Amphibia, Caudata, Hynobiidae) from western Japan - Tominaga, Atsushi; Matsui, Masafumi; Nishikawa, Kanto (Zootaxa, 2019)
Two new species of lotic-breeding salamanders, Hynobius sematonotos and H. oyamai, are described from Chugoku district and northeastern Kyushu district, respectively, western Japan. They are members of the so-called H. naevius group and are phylogenetically close to H. naevius, H. katoi, and H. hirosei but divergent from them with large genetic distances. These new species have been treated as Chugoku and northeastern Kyushu lineages, respectively, of H. naevius to which they are morphologically very similar. However, these new species can be differentiated from H. naevius by several morphological traits. Hynobius sematonotos is characterized and discriminated from other species by combination of small body size, a shallow vomerine teeth series with small number of vomerine teeth, small number of upper and lower jaw teeth, relatively long head and snout, and large upper eyelid, relatively short axilla-groin, reddish purple ground color with grayish brown marking on the dorsum, and reddish to bluish gray ventral ground color with relatively large markings varying from pale-white to white. Hynobius oyamai is characterized and discriminated from other species by large body size, moderately deep vomerine teeth series with a medium number of vomerine teeth, large number of upper and lower jaw teeth, relatively wide internarial and long fifth toe, bluish purple ground color sometimes with pale white marking on dorsum. Hynobius sematonotos occurs in Honshu, disjunct from H. naevius and H. oyamai that occur allopatrically in Kyushu.